Back to their roots: French MPs in their district. Issue 4 (December 2016) - Costa, Olivier; Poyet, Corentin
Abstract The aim of this article was to investigate the district work of members of the French National Assembly (MPs), namely their contacts with citizens and other kinds of actors on the ground. Based on original data, our results show that the MPs' constituency work is somewhat disconnected from the national political debate. They are close to their constituents and meet them regularly in surgeries or during local celebrations and events. Issues discussed are mainly oriented towards individual and local needs (housing, employment, etc.). A multivariate analysis highlights the different patterns of district work. Overall, this article suggests that district features and the MPs' individual characteristics shape their behaviour in their constituency. By exploring the concrete practices of French MPs at home, this article offers new insights into parliamentary representation and into the different logics that underlie district work.